2020
DOI: 10.1158/2326-6066.cir-19-0574
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T-cell Immunity in the Peripheral Blood Correlates with Response to Anti-PD-1 Therapy

Abstract: ◥ Accumulating evidence indicates that CD8 þ T cells in the tumor microenvironment and systemic CD4 þ T-cell immunity play an important role in mediating durable antitumor responses. We longitudinally examined T-cell immunity in the peripheral blood of patients with non-small lung cancer and found that responders had significantly (P < 0.0001) higher percentages of effector, CD62L low CD4 þ T cells prior to PD-1 blockade. Conversely, the percentage of CD25 þ FOXP3 þ CD4 þ T cells was significantly (P ¼ 0.034) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
170
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(192 citation statements)
references
References 40 publications
20
170
1
1
Order By: Relevance
“…Moreover, highly differentiated CD4 T cells corresponded to both central and effector memory cells but not to senescent or exhausted cells. Our results were also in very close agreement by a detailed and complete study carried out by Kagamu et al These authors used mass cytometry and found that NSCLC patients responding to nivolumab had a significantly higher percentage of CD62L low CD4 T cells than non-responders at baseline [34]. Interestingly, these T cells were also double negative in CD27 and CD28, and corresponded to memory subsets.…”
Section: Cd4 T Cellssupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, highly differentiated CD4 T cells corresponded to both central and effector memory cells but not to senescent or exhausted cells. Our results were also in very close agreement by a detailed and complete study carried out by Kagamu et al These authors used mass cytometry and found that NSCLC patients responding to nivolumab had a significantly higher percentage of CD62L low CD4 T cells than non-responders at baseline [34]. Interestingly, these T cells were also double negative in CD27 and CD28, and corresponded to memory subsets.…”
Section: Cd4 T Cellssupporting
confidence: 90%
“…Tregs promote immunosuppression and tolerance once infiltrated into the TME. Accordingly, a decrease in peripheral blood Tregs after ipilimumab treatment in metastatic melanoma patients was associated to disease control and OS [36], while the baseline percentage of CD25 + FoxP3 + CD4 T cells in NSCLC patients treated with nivolumab was higher in non-responders [34]. These results overall suggest that a decrease of this immunosuppressive population contributes to the efficacy of ICI therapies.…”
Section: Cd4 T Cellsmentioning
confidence: 72%
“…These results highlighted the up-regulation of LAG-3 as a major escape mechanism to PD-1/PD-L1 monoblockade strategies. Very similar results were obtained in two other independent studies by Kagamu and collaborators, and Julia and collaborators (Julia et al, 2019;Kagamu et al, 2020). In the study by Zuazo et al responders had a high percentage of highly differentiated CD27 − CD28 − memory CD4 T cells before starting immunotherapies, and could be used as a predictive biomarker.…”
Section: Tumor-extrinsic Factors and Resistance To Pd-l1/pd-1 Blockadsupporting
confidence: 79%
“…The first study correlated the high baseline frequency of central memory CD4 T cells with response to immunotherapy in NSCLC and renal cancer patients using flow cytometry (Julia et al, 2019). In the second study, NSCLC patients with high baseline percentages of CD62L low effector CD4 T cells quantified by CyTOF had a high chance of responding to PD-L1/PD-1 blockade (Kagamu et al, 2020). The dynamics and behavior of these CD4 T cell subsets were identical to those from highly-differentiated memory CD4 T cells in our study, strongly suggesting that we were all monitoring the same CD4 T cell subsets but with different markers.…”
Section: Discussionmentioning
confidence: 99%
“…Some, such as increases in the frequency of immunosuppressive cells like CD4+ regulatory T-cells (T-regs), are associated with a worse prognosis 11 . Other changes, such as altered T-cell differentiation status, are associated with increased clinical response after immunotherapy 12 . NK cells in adult cancer patients are unaltered in frequency but are less cytotoxic 13 , 14 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%